2021
DOI: 10.1563/aaid-joi-d-21-00023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Implant Length and Diameter on Stress Distribution of Tooth-Implant and Implant Supported Fixed Prostheses: An In Vitro Finite Element Analysis Study

Abstract: The aim of this study is to evaluate the effectiveness of the implant diameter and length on force dissemination of tooth-implant and implant retained fixed restorations. A finite analysis model was used via a 3D simulation of a unilateral mandibular Kennedy Class I arch. Through thresholding the resultant assembly, a region of interest was selected from the CT scan. Details of the diameter (D) and length (L) of implant were introduced. Ds used were 3.7, 4.7, and 5.7, while Ls used were 10, 11.5, and 13. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This can be interpreted by the non-rigid connection's function to divide the prosthesis into two different parts; a single crown on the tooth and a cantilever on the implant side resulting in less stress on the tooth itself but increased unfavorable stresses on the prosthesis as well as tooth intrusion. [34][35][36][37][38] In addition the findings complement those of Naguib et al, 18 in regard to stress dissemination, where the diameter of the implant was more pivotal than its length.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…This can be interpreted by the non-rigid connection's function to divide the prosthesis into two different parts; a single crown on the tooth and a cantilever on the implant side resulting in less stress on the tooth itself but increased unfavorable stresses on the prosthesis as well as tooth intrusion. [34][35][36][37][38] In addition the findings complement those of Naguib et al, 18 in regard to stress dissemination, where the diameter of the implant was more pivotal than its length.…”
Section: Discussionsupporting
confidence: 76%
“…29 This study commenced from previously published work that investigated the significance of implant length and diameter on stress dissemination in tooth-implant fixed dental prosthesis with rigid connection design. Naguib et al, 18 concluded that the increase in implant diameter with a proportionate increase in length was directly related to reduced stress on the prostheses. The main focus of this study was to evaluate different connector designs as an input variable through showing the magnitude of Von Misses stress Contrary to previous research studies supporting non-rigid FDPs that exhibit the least amount of stress and favorable prognosis to the tooth abutment in a tooth-implant FDP, 19,[30][31][32][33] our results demonstrated that FDPs with rigid connection showed considerably lower mean stress values than those with non-rigid connection design.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations